Paraganglioma of bladder - A case report and review of literature - Naime, Fauzia de Fátima (2022)
A case of rare functioning urinary bladder paraganglioma, secretive and metastatic to the bone, is presented with a review of the literature. Paragangliomas are tumours arising from paraganglionic cells disperded along  the autonomous ganglia and that produce symptoms by secreting catecholamines (functioning tumours) or by local tumours invasion. They metastasize to bones, Iungs, lymphnodes, brain and occasionaly comprise spinal cord compression. Paragangliomas of bladder represent about 0,06% of all bladder tumours and affect most commonly the trigone or near the ureteral orifices, followed by bladder dome and lateral walls. The classic micturicional syndrome consisting of headache, palpitation, paroxysmal hvpertension and hematuria is discussed, and clinical, radiological, and pathologic findings are summarized. General principies of diagnosis and treatment are also discussed taking into consideration all available therapeutic approaches, which include surgerv, radiation therapy chemotherapy, and in recent years metaiodobenzylguanidine.